INNOVATION IN EDUCATION: PREVENTION AND CORRECTION OF THE PEDIOGENIAS AND MATETOGENIAS IN STUDENTS AND TEACHERS - Kassymova G. K.; Valeeva G. V; Muller O. Yu.; Anufrieva N. V.; Arpentieva M. R.; Lavrinenko S. V.; Dossayeva S. K (Scientific Journal of Pedagogy and Economics, 2019)
This paper deals with stress, which is one of the major problem for students and teachers throughout the innovation in education. The focus of this investigation is the prevention and correction of the pediogenias and matetogenias in students and teachers. These didactogenias take part information of the personal, interpersonal and organizational stress disorders and crisis. Stress is a significant problem in our times and affects the physical, mental, social andmoralhealth of people. The main objectives are to ascertain the extent to which innovations in university and schools stress affects students’ academic and professional success, and their personal, interpersonal and organizational health/ The authors is suggest some techniques and practices to cope with stress for students and teachers. Stress coping methods are the moral, social, physiological, and psychological. Authors outline and suggest the different methods to deal with stress (to its prevention and coping). There are many effective and productive stress management techniques. These stress management techniques students and teachers are need to practice during the lessons and in special activities in the schools and universities and in other situations. In addition to educational and professional stress, it is important to take into account the stresses of personal development and interpersonal relations, which are associated with the “private” or “intimate-personal” as well as social aspects and layers of relationships in human life. The authors introduce the concept of stress innovation. The stress of innovation is the stress that occurs in the process and result of the introduction of innovation. For students and teachers, innovation is both a situation that generates stresses and crises of the personal, interpersonal and organizational levels, and a way to overcome such stresses, problems, and development crises. It is important to note the relationship of causes and consequences, as well as the manifestations of stress of teachers and students at the personal, interactive, educational and organizational levels.